Intergenerational spillover effects of antiretroviral therapy in sub-Saharan Africa: a scoping review and future directions for research - Schröder, Henning; Yapa, H. Manisha; Gómes-Olivé, F. Xavier; Thirumurthy, Harsha; Seeley, Janet; Bärnighausen, Till; De Neve, Jan-Walter (BMJ global health, 2023)
Background Antiretroviral therapy (ART) may influence individuals who do not receive the intervention but who are connected in some way to the person who does. Relatively little is known, however, about the size and scope of, what we term, spillover effects of ART. We explored intergenerational spillover effects of ART in sub-Saharan Africa (SSA) and identified several directions for future research. - Methods We conducted a scoping review between March and April 2022. We systematically searched PubMed, PsycINFO, EconLit, OTseeker, AIDSInfo, Web of Science, CINHAL, Google Scholar and African Index Medicus. We analysed the distribution of included studies over time and summarised their findings. We examined the intergenerational impact of ART provision to working-age adults living with HIV on children (‘downward’ spillover effects) and older adults (‘upward’ spillover effects). We categorised types of intergenerational spillover effects according to broad themes which emerged from our analysis of included studies. - Findings We identified 26 studies published between 2005 and 2022 with 16 studies assessing spillover effects from adults to children (downward), and 1 study explicitly assessing spillover effects from working-age adults to older adults (upward). The remaining studies did not fully specify the direction of spillover effects. Most spillover effects of ART to household and family members were beneficial and included improvements in wealth, labour market outcomes, health outcomes and health services utilisation, schooling, and household composition. Both children and older adults benefited from ART availability among adults. Detrimental spillover effects were only reported in three studies and included financial and opportunity costs associated with health services utilisation and food insecurity in the first year after ART. - Conclusions ART may lead to substantial spillover effects across generations and sectors in SSA. Further research is needed to capitalise on positive spillover effects while mitigating potential negative spillover effects. The returns to investments in large-scale health interventions such as ART may be underestimated without considering these societal benefits.
Gesehen am 18.04.2023